An innovative antimicrobial stewardship programme for children in remote and regional areas in Queensland, Australia: optimising antibiotic use through timely intravenous-to-oral switch. (March 2022) - Avent, M.L.; Lee, X.J.; Irwin, A.D.; Graham, N.; Brain, D.; Fejzic, J.; van Driel, M.; Clark, J.E.
Highlights: Programmes that optimise timely intravenous (IV)-to-oral antibiotic switch may limit excessive in-hospital antibiotic use. Paediatric tertiary care facilities have shown a reduction in IV antibiotic duration. Reduced IV antibiotic duration results in shorter hospital length of stay. A multifaceted intervention package to enhance timely IV-to-oral switch for children in remote facilities is effective. ABSTRACT: Objectives: Little is known about the benefits of timely switch from intravenous (IV) to oral antibiotic therapy in children. We evaluated the appropriateness of IV-to-oral switch of antibiotic therapy in remote and regional areas of Australia following the implementation of a multifaceted package of interventions. Methods: The intervention package, including clinician guidelines, medication review stickers, patient information leaflets and educational resources, was implemented in seven facilities in Queensland, Australia. Children with community-acquired pneumonia and skin and soft-tissue infections were switched to oral therapy if they met the required 'IV-to-oral switch' criteria. Data were collected for a 7-month period from May to November for the baseline (2018) and intervention (2019) phases. Results: A total of 357 patients were enrolled in the study, including 178 in the baseline phase and 179 in the intervention phase. The percentage of patients who switched to oral therapy or stopped IV antibiotics, within 24 h of eligibility, increased from 87.6% (156/178) in the baseline phase to 97.2% (174/179) in the intervention phase ( P  = 0.003). The average number of extra IV days decreased from 0.45 days in the baseline period to 0.18 days in the intervention period ( P < 0.001). The median patient length of stay was 2 days for both phases. The only adverse events recorded were line-associated infiltration, with a decrease from 34.3% (61/178) (baseline) to 17.9% (32/179) (intervention) ( P < 0.001). Conclusion: A multifaceted intervention package to enhance timely IV-to-oral switch of antibiotic therapy for children in remote and regional facilities is effective.